2019
DOI: 10.1108/tr-08-2018-0116
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risks, travel constraints and visit intention of young women travelers: the moderating role of travel motivation

Abstract: Purpose This study aims to investigate the moderating effect of travel motivation on the relationship between perceived risks, travel constraints and visit intention of young women travelers. Design/methodology/approach A quantitative study was performed, and data were collected from 416 female university students using convenience sampling. Structural equation modeling with partial least square approach was used to test the research hypotheses. Findings The findings revealed that travel motivation has a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 99 publications
(163 reference statements)
7
84
0
10
Order By: Relevance
“…This idea leads to the acceptance of hypotheses one, two, three and four. However, the relationships of the dimensions of risk perception sometimes are inconsistent with the intention to visit a destination such as in Khan et al (2019). The researchers also found that financial risk and time risk had no significant influence towards Predictors: social risk, physical risk, psychological risk, performance risk, financial risk, time risk, and stress level Source: HMR Analysis, 2020 the respondents' intentions for post-pandemic international travel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This idea leads to the acceptance of hypotheses one, two, three and four. However, the relationships of the dimensions of risk perception sometimes are inconsistent with the intention to visit a destination such as in Khan et al (2019). The researchers also found that financial risk and time risk had no significant influence towards Predictors: social risk, physical risk, psychological risk, performance risk, financial risk, time risk, and stress level Source: HMR Analysis, 2020 the respondents' intentions for post-pandemic international travel.…”
Section: Discussionmentioning
confidence: 99%
“…The risk is considered as an essential factor that influences tourist's behavior, as tourism is an intangible service that is exposed to potential risks and threats (Hashim et al, 2018). A single harmful incidence can change the perception of risk associated with a destination and decrease tourist arrivals (Chew & Jahari, 2014;Carter, 1998;Khan et al, 2019). The tourists might doubt that the product or service cannot meet their expectations or that is the collection of factors, which are beyond the control during the consumption process (An & Fu, 2005;Cui et al, 2016).…”
Section: Risk Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Travel constraints memiliki definisi yang berbeda dengan risk (risiko). Menurut Khan et al, (2019) risiko (risk) didefinisikan sebagai suatu ketidakpastian dan konsekuensi negatif dari pembelian produk atau layanan. Maka dari itu risiko merupakan akibat dari suatu tindakan sedangkan travel constraints (hambatan perjalanan) merupakan sebab seseorang dapat membatalkan niat pembelian atau berkunjung ke suatu objek wisata.…”
Section: E-wom (Word Of Mouth)unclassified
“…Menurut Khan et al, (2019) travel constraints memiliki arti sebagai variabel dan menjelaskan mengenai hambatan yang dapat timbul seperti waktu, uang, peluang, pengetahuan, kemampuan, kepadatan penduduk, kurangnya pasangan, rasa malu, kurangnya transportasi, keselamatan, minat dan kualitas buruk yang dapat mencegah seseorang dalam kegiatan berwisata. Berdasarkan penelitian yang dilakukan oleh (Hung & Petrick, 2012) terdapat hasil yang berpengaruh negatif antara travel constraints dan niat berkunjung.…”
Section: Travel Constraintsunclassified